2020
DOI: 10.3390/cancers12030602
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Immunoprofiles of Renal Cell Carcinoma Subtypes

Abstract: In recent years, renal epithelial tumors have been among the fastest reclassifying tumors, requiring updates to the tumor classification system. Nonetheless, immunohistochemistry (IHC) remains the most widely used tool for renal epithelial tumors. In this proposal, we aimed to create the most efficient IHC panel for categorizing the diverse subtypes of renal tumors, and to find out more specific immunohistochemical results in each subtype or each antibody. A total of 214 renal tumors were analyzed using 10 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Afterward, an interventional radiology biopsy of the left-sided renal mass revealed invasive RCC with clear cell features associated with extensive necrosis. An immunohistological evaluation showed that the biopsy was positive for CD10, vimentin, and Pax8 [ 13 , 14 ], which confirmed the diagnosis of renal origin.…”
Section: Discussionmentioning
confidence: 94%
“…Afterward, an interventional radiology biopsy of the left-sided renal mass revealed invasive RCC with clear cell features associated with extensive necrosis. An immunohistological evaluation showed that the biopsy was positive for CD10, vimentin, and Pax8 [ 13 , 14 ], which confirmed the diagnosis of renal origin.…”
Section: Discussionmentioning
confidence: 94%
“…Immunostaining for vimentin was invariably extensive as is typical for human tissues of mesenchymal origin. The accompanying positivity for CD10 in three of the 10 rat tumours could fit for humans [ 10 ]. MNF 116 positivity seems to be a useful characteristic for some rat renal tumours but does not feature for human renal cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of DDX3X is altered in part by its interactive molecules [9]. The results of a recent study showing the comprehensive immunoprofiles of renal cell carcinoma subtypes illustrated the possible reason [24]. The major difference was uncovered and shown that the c-kit protein was positively expressed in renal chromophobe, while its expression level was negative in renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%